A bibliometric review on voluntary childlessness in marriage from the Islamic perspective - Duasa, Jarita; Zulkifli, Izyani; Idris, Zera Zuryana (IKIM Press, 2025)
This study presents a comprehensive bibliometric analysis of scholarly research on voluntary childlessness from an Islamic perspective, covering the period from 1969 to 2024. Using SCOPUS-indexed publications, it examines temporal trends, citation patterns, thematic developments, and influential contributors. Voluntary childlessness—defined as the conscious choice to remain childfree—has gained increasing global relevance, intersecting with ethical, cultural, and religious considerations. In Islamic contexts, where family and procreation hold central moral and social importance, this subject presents particular complexities. The analysis reveals a modest but growing body of literature, with key themes including gender roles, religious norms, policy discourse, ethical considerations, and socioeconomic influences. Despite limited publication volume and minimal international collaboration, citation metrics reflect meaningful academic engagement. The findings highlight the need to frame discussions on family planning within Islamic ethical frameworks and cultural sensibilities. The study concludes by recommending greater interdisciplinary engagement, deeper integration of Islamic jurisprudential perspectives, and expanded global collaboration to strengthen and diversify research in this evolving field